Estudo do espectro Raman vibracional anarmônico de sistemas moleculares isolados através dos métodos VSCF e VCI - Carvalho, Jhonatas Rodrigues de (2021)
In the present study, the influence of anharmonicity on the fundamental, overtone and combination Raman transitions is assessed through the use of the Vibrational Self-Consistent Field (VSCF) and Vibrational Configuration Interaction (VCI) methods. For that purpose, a set of algebraic expressions was developed to represent the transition polarizability tensor and the corresponding Raman cross section within the VSCF and VCI approaches. In order to enable the evaluation of the Raman spectrum at the VSCF and VCI levels, those expressions were implemented in a Fortran code, named as VSCFR. The VSCFR program can represent the system’s Potential Energy Surface (PES) in one of the following ways: (i) Polynomial Function, through a Taylor series involving quadratic, cubic and quartic force constants; (ii) By means of the n-mode numeric representation. The geometry optimization and force constant calculations were performed at the CCSD(T)/aug-cc-pVTZ level and the dynamic electronic polarizability surface was described at the CC3/aug-cc-pVTZ level. Unless otherwise specified, all electronic structure calculations were done using the frozen-core approximation. Program CFOUR was selected to perform those calculations. The VSCF modals were expanded as linear combinations of unidimensional harmonic functions. Regarding the Raman shifts, our results show that, in general, the anharmonic data are in better agreement with the experiment than the corresponding harmonic data. On the other hand, only the VSCF cross sections for the fundamental transtions of acetylene and its deuterated isotopologues are in better agreement with the experimental data while the cross sections of combination and overtone transitions are not improved through the use of anharmonic models. In addition, the fundamental transitions of H2O, CHD3 e CH2D2 are not improved by the anharmonic models as well.